HUBUNGAN UMUR DAN PARITAS IBU TERHADAP KEJADIAN PREEKLAMPSIA PADA IBU BERSALIN DI RSUD ARIFIN ACHMAD PEKANBARU - Emi Yulita (Ensiklopedia of Journal, 2021)
Preeclampsia is the onset of hypertension accompanied by proteinuria and edema due to pregnancy after 20 weeks' gestation or immediately after delivery. The purpose of this study was to determine the relationship of age and parity to the occurrence of preeclampsia in maternity mothers. The design of this study was cross sectional analytic. The research sample of 260 respondents, namely maternity mothers who experienced preeclampsia at Arifin Achmad Hospital in Pekanbaru with a sample of 130 maternity women who experienced preeclampsia. Sampling is done randomly using simple random sampling technique. Univariate research results found that based on the age group the majority of respondents were in the age group at risk with the number of 69 respondents (53.1%),). While based on parity the majority of respondents were in the parity group at risk with a number of 87 respondents (66.9%). The analysis found that there was a significant relationship between maternal age with the incidence of preeclampsia with statistical tests obtained p value of 0.012 <0.05 and there was a significant relationship significant between maternal parity with the incidence of preeclampsia with a statistical test p value of 0,000 <0.05. It is recommended that health workers provide counseling about preeclampsia to maternity mothers